2010
DOI: 10.1590/s0104-42302010000300022
|View full text |Cite
|
Sign up to set email alerts
|

"Sling" retropúbico e transobturatório no tratamento da incontinênca urinária de esforço

Abstract: Objective. To compare the results of retropubic and transobturator slings for surgical treatment of female stress urinary incontinence (SUI). MethOds. We randomized thirty patients with SUI, ten of whom underwent transobturator sling surgery and ten retropubic sling surgery. Patients were assessed before treatment and 1, 6 and 12 months after treatment on the basis of clinical history, physical examination, quality of life questionnaire (King's Health Questionnaire), pad test and urodynamic evaluation. The gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 23 publications
0
4
0
2
Order By: Relevance
“…In two previously discussed articles Gomes and da Silva1 described prevalence of stress urinary incontinence in women over 20 years of age, who participate in the Family Health Program in the city of Dourados, State of Mato Grosso do Sul, Brazil and conclude that prevalence is similar to that of other studies. Tanuri et al2 compared results of retropubic and transobturator sling for surgical treatment of female stress urinary incontinence which were effective at one-year follow-up. Oliveira et al72 evaluated risk factors related to occurrence of female urinary incontinence and found that independent risk factors include age, vaginal delivery, forceps delivery, and weight of largest infant and as a protective factor, cesarean section delivery.…”
Section: Reviewmentioning
confidence: 99%
“…In two previously discussed articles Gomes and da Silva1 described prevalence of stress urinary incontinence in women over 20 years of age, who participate in the Family Health Program in the city of Dourados, State of Mato Grosso do Sul, Brazil and conclude that prevalence is similar to that of other studies. Tanuri et al2 compared results of retropubic and transobturator sling for surgical treatment of female stress urinary incontinence which were effective at one-year follow-up. Oliveira et al72 evaluated risk factors related to occurrence of female urinary incontinence and found that independent risk factors include age, vaginal delivery, forceps delivery, and weight of largest infant and as a protective factor, cesarean section delivery.…”
Section: Reviewmentioning
confidence: 99%
“…The major benign gynecological conditions with surgical indication are uterine myoma and urinary incontinence. While in specialized centers they are treated today with minimally invasive techniques, in centers distant from large capitals the conventional surgical treatments dominate 2,5 .…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…Urinary incontinence (UI), on its turn, represents about 10% of gynecological complaints [5][6][7][8][9][10] . The operative techniques of suburethral sling for correction of UI can use a wide variety of autologous and synthetic materials and consist of the use of a strip positioned inferiorly to the urethra or bladder neck without tension.…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%
See 1 more Smart Citation
“…Alguns pontos são importantes para o correto diagnóstico da doença, tal como a coleta de uma história clínica detalhada, em que se investiga o grau de vazamento, o tempo de início, os detalhes da história pregressa cirúrgica e obstétrica da paciente, bem como as medicações em uso e as comorbidades sistêmicas que lhe acomete. Ao exame físico, deve-se analisar, em região ginecológica, a existência de alterações como lassidão do suporte pélvico, mobilidade de parede vaginal anterior, presença de algum grau de prolapso, cistocele, retocele, alterações tróficas relacionadas ao estímulo hormonal e status neurológico da pelve (distúrbios de sensibilidade ou hipotonias severas) (MCANINCH & LUE, 2014;TANURI et al, 2010).…”
Section: Pré-operatório E Critérios De Inclusãounclassified